APLIKASI THEORY OF REASONED ACTION UNTUK MEMPREDIKSI PERILAKU KONSUMEN UNTUK PEMBELIAN SEPEDA MOTOR HONDA VARIO (Studi Kasus : Mahasiswa Fakultas Ekonomi Unika Santo Thomas Medan) - Simanihuruk, Peran (Jurnal Manajemen dan Bisnis, 2013)
This study analyzes the Consumer Behaviour In Buying Motorcycles Honda Vario. Objective to investigate the influence of consumer confidence and the evaluation will result in a partial and simultaneous on consumer attitudes, to determine the effect of normative beliefs and motivations of consumers and simultaneously to partially subjective norms, to determine the effect of consumer attitudes and subjective norms, and simultaneous partial to behave interests . The benefits of research to provide inputs for the company in formulating and developing marketing strategies. to contribute to other researchers in the development of the theory of consumer behavior developed by I. Ajzen and M. Fishbein. Total sample of 125 respondents, the type of data used primary and secondary data and data collection tools and documentation koesioner. Data analysis tools used multiple regression.. The results showed consumer confidence coefficient and evaluation will have nalai positive effect on consumer attitudes, normative beliefs and motivation variables consumers have a positive value on subjective norms, as well as variables in consumer attitudes and subjective norms have positive value to the interest behave. Based on t test and F test showed that consumer confidence and the evaluation will have a significant effect partially and simultaneously on consumer attitudes, normative beliefs and motivations of consumers having a significant effect on partial and simultaneous subjective norms, consumer attitudes and subjective norms have an influence significant and simultaneous partial to behave interest to buy a motorcycle Handa Vario.